Burnout and mental health problems among health care workers during second wave of Covid-19 pandemic: A hospital based cross sectional study - Bhattarai, Nirajan; Maharjan, Mankeshari; Bhatta, Chet Raj; Niraula, Hira Kumari; Thapa, Pradeep (Journal of Psychiatrists' Association of Nepal, 2023)
Background: Large number of healthcare workers exposed to COVID-19 might be at increased risk of developing mental and psychological disorders. This study aimed to find out the prevalence of burnout, depression, anxiety and stress and its correlates. Methods: This was hospital based cross-sectional study using printed Questionnaire conducted during second wave of COVID-19. Total 96 healthcare workers participated in this study. Depression Anxiety Stress Scale (DASS-21) and Copenhagen Burnout Inventory (CBI) were used to measure study variables. Multivariable logistic regression analysis was done to determine the associate factors. Results: The symptoms of depression, anxiety and stress were found to be 31.3%, 40.6 % and 14.6 % respectively. Doctors were 5.2 and 6 fold more likely to experience anxiety and depression respectively. The prevalence of personal, work, and client-related burnout were 43.7%, 31.3% and 14.6% respectively. Younger healthcare workers (HCWs) less than 27 years were 3.5 fold more likely to develop personal burnout. Healthcare workers who had worked for more than 100 hours/week were 5 times more likely to experience personal burnout. Doctors and nurses were 7.9 and 3.5 times more likely to develop work related burnout. Personal, work and client related burnout were significantly correlated with anxiety. Conclusion: This study finds considerate proportion of burnout, depression, anxiety and stress among HCWs. Doctors and younger HCWs with increased working hours had high level of these symptoms. Early identification of mental health disorders and awareness intervention could increase the efficiency and quality of care.